New perspectives on recycling waste glass in manufacturing concrete for sustainable civil infrastructure. (10th October 2020) - Guo, Pengwei; Meng, Weina; Nassif, Hani; Gou, Hongye; Bao, Yi
Highlights: This review clarifies the debates on the effects of glass particles on concrete properties. The effects of glass on concrete properties depend on glass particle size and percentage. Appropriate use of glass can improve the flowability and mechanical strength of concrete. Using glass can improve the permeability and freezing-thawing resistance of concrete. Reducing glass particle size is effective in suppressing ASR expansion. Abstract: While a large amount of waste glass is annually produced worldwide, a limited percentage of waste glass is recycled. Recycling glass in concrete has shown great promise in solid waste management because there is a high volume of concrete in civil infrastructure. However, a consensus on the effects of waste glass in concrete has not been achieved. Some researchers reported that the use of waste glass improved the properties of concrete, but some researchers reported opposite results. The inconsistent results of the effect of waste glass hinder the acceptance of glass in producing concrete. This review aims to clarify the debates and attempts to elucidate the opposite viewpoints. To this end, this paper reviews different results reported by different research groups and proposes new perspectives based on analyzing underlying mechanisms, considering different types of waste glass, including soda-lime, electric, lead, and borosilicate glass. The reviewed contents include the fresh properties, compressive strength, durability, thermal properties, electrical properties, and microstructure of concrete. This review is expected to advance the knowledge of recycling glass in producing concrete, point out future research needs, and facilitate wider adoption of waste glass concrete in developing sustainable and durable infrastructure.